2014
DOI: 10.3390/jpm4020282
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptome Profile of Peripheral White Cells to Identify Biomarkers Involved in Oxaliplatin Induced Neuropathy

Abstract: Anticancer chemotherapy (CT) produces non-desirable effects on normal healthy cells and tissues. Oxaliplatin is widely used in the treatment of colorectal cancer and responsible for the development of sensory neuropathy in varying degrees, from complete tolerance to chronic neuropathic symptoms. We studied the differential gene expression of peripheral leukocytes in patients receiving oxaliplatin-based chemotherapy to find genes and pathways involved in oxaliplatin-induced peripheral neuropathy. Circulating wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Previous research from our group has led to the identification of several genes, which were shown to be significantly up-, or down- regulated in peripheral white cells (PWCs) of CRC patients, due to oxaliplatin-based chemotherapy (Morales et al, 2014 ). Interestingly, one of the differentially expressed genes was the isoform α3 of the Na,K-ATPase ; mRNA levels of Na,K-ATPase α3 subunit were down-regulated 2.6-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research from our group has led to the identification of several genes, which were shown to be significantly up-, or down- regulated in peripheral white cells (PWCs) of CRC patients, due to oxaliplatin-based chemotherapy (Morales et al, 2014 ). Interestingly, one of the differentially expressed genes was the isoform α3 of the Na,K-ATPase ; mRNA levels of Na,K-ATPase α3 subunit were down-regulated 2.6-fold.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous screening for biomarkers involved in oxaliplatin toxicity, FKBP5 was the gene whose transcriptional expression level was most downregulated quantitatively ( 5 ). In the current study, IHC analysis of FKBP51 protein expression and localization allowed observation of strong staining in the nuclei of enterocytes in healthy colon, whereas in colonic adenocarcinoma cells, the staining was localized in nuclei and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of biomarkers that could predict the onset of these secondary effects would be of great value in preventing long-term toxicity or permanent damage in patients at risk. Recent research from our laboratory has led to the identification of several genes that are significantly up- or downregulated in peripheral white cells (PWCs) of CRC patients following oxaliplatin-based chemotherapy treatment ( 5 ). In our screening, the expression levels of the gene encoding for the immunophilin FK506-binding protein 5 (FKBP51) were 2.76-times lower [3,812 (pre) vs. 1,383 (post)] in PWCs after 3 cycles of oxaliplatin-based chemotherapy ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to identify biomarkers that may predict the onset of these secondary effects, a recent study investigated the differential gene expression of peripheral leukocytes in patients with CRC prior to and following 3 cycles of oxaliplatin-based CT ( 3 ). The study identified 502 differentially-expressed genes that were significantly up- or downregulated in the peripheral white cells (PWCs) of patients following CT treatment ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the changes in gene expression observed in PWCs may be detected in tumors following the administration of adjuvant CT, the present study performed immunohistochemical analysis of a selected number of genes that had previously been identified in the differential transcriptome profile ( 4 ). The study observed that one gene among four, whose transcriptional expression levels varied from ‘off’ to ‘on’, was that coding for IQ-motif containing GTPase activating protein 1 (IQGAP1) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%